2020
DOI: 10.1038/s41598-020-64024-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns Associated to Clinical Aspects in Crohn’s Disease Patients

Abstract: Diet is an important factor in both the pathogenesis and in the clinical course of Crohn's disease (CD). However, data on dietary patterns of CD patients are rather limited in the literature. This cross-sectional study included 60 patients with CD, aged 18-60 years. Dietary intake was assessed using a validated food frequency questionnaire to measure food consumption patterns by principal component analysis (PCA). Multiple regression analysis was performed to investigate the association between dietary pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…Unlike most studies, the perceived effects of coffee and tea were investigated individually, where coffee was frequently associated with symptom onset and exacerbation, and black tea was well tolerated. Generally, tea and coffee appear to be problematic as evidenced by their association with increased risk of relapse [ 15 ], negative effects on symptoms [ 48 ], significantly reduced consumption in CD patients experiencing active disease [ 60 ], and overall avoidance [ 16 , 58 ]. However, taking into account de Vries et al’s [ 32 ] observation that tea is the second most symptom improving food among 294 patients with IBD, and the findings of the present study, coffee and tea should be considered separately when investigating their purported effects on IBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most studies, the perceived effects of coffee and tea were investigated individually, where coffee was frequently associated with symptom onset and exacerbation, and black tea was well tolerated. Generally, tea and coffee appear to be problematic as evidenced by their association with increased risk of relapse [ 15 ], negative effects on symptoms [ 48 ], significantly reduced consumption in CD patients experiencing active disease [ 60 ], and overall avoidance [ 16 , 58 ]. However, taking into account de Vries et al’s [ 32 ] observation that tea is the second most symptom improving food among 294 patients with IBD, and the findings of the present study, coffee and tea should be considered separately when investigating their purported effects on IBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Using machine learning on food group-based analysis, we showed that a dietary pattern consisting of cereal and meat-based products could successfully predict the assignment of 92% of patients into their respective FC group. In a recent cross-sectional study of patients with CD, principal component analysis also identi ed that a dietary pattern rich in rice, pasta and red meat, among other foods, was associated with increased symptom frequency, but did not differentiate patients with active disease from those in remission (34). In the current study, patients with higher FC levels also reported a higher consumption of gluten containing cereal products, which points to gluten-containing foods as potential driver of intestinal in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is an important nutritional factor to be taken into account when assessing the impact of nutrients, as well as the existence of dietary patterns involved in both the pathogenesis and the clinical progression of IBD. Recent dietary research has shown that whole dietary patterns are more representative and more important than isolated individual nutrient evaluations[ 54 ].…”
Section: Specific Diets On Ibdmentioning
confidence: 99%
“…These patterns are: (1) “Traditional + FODMAP”; (2) “fitness style”; and (3) “snacks and processed foods”. These patterns can be considered good indicators of patients’ eating habits, and facilitate the understanding of the relationship between diets and diseases[ 54 ]. Therefore, in general, results of dietary pattern studies should be considered when providing nutritional counseling to patients.…”
Section: Specific Diets On Ibdmentioning
confidence: 99%